New records on synanthropic spider species (Arachnida: Araneae) in Slovenia - Rok Kostanjšek; Ana Celestina (Natura Sloveniae)
Four spider species, Dictyna civica (Lucas 1850) (Dictynidae), Philodromus praedatus O. P. Cambridge 1871 (Philodromidae), Cheiracanthium mildei L. Koch 1864 (Miturgidae) and Clubiona similis L. Koch 1867 (Clubionidae), new for Slovenian fauna, have been recorded on bridges over the Ljubljanica river and on buildings in the centre of Ljubljana